Association of Dental Caries and Anthropometric Measures among Primary School Children - Wajiha Anzar; Ambrina Qureshi; Ashar Afaq; Hiba F. Kattan; Basil Almutairi; Khaled M. Alzahrani; Mustafa Naseem; Fahim Vohra; Tariq Abduljabbar (MDPI AG, 2021)
Aim: This study aimed to investigate an association between dental caries status and anthropometric measures in primary school children. Methods and Materials: An analytical cross-sectional study (n = 376) was conducted among primary school children (age range = 6-9 years) registered in private schools. Non-clinical data was gathered from parents of participating children through a self-administered structured questionnaire as well as from the children through an interviewer-administered questionnaire. Clinical data included the examination of dental caries using dmft/DMFT index and anthropometric measures including calculated z-scores of height-for-age (HAZ), weight-for-age (WAZ), BMI-for-age (BAZ), and physical examination. Inferential statistics included Kruskal Wallis and linear regression for univariate and multivariate analysis respectively. Results: The proportion of dental caries in primary and secondary dentition was 67.6% and 8.2% respectively. A significant association was observed between dental caries status and HAZ, WAZ, and BAZ (p < 0.001). An inverse relation was found between low, medium, and high dental caries categories and anthropometric measures. Conclusions: In the primary dentition, dental caries were significantly and inversely related to weight-for-age, height-for-age, and BMI-for-age. Hence, it can be concluded that among the low-income population dental caries is associated with lower anthropometric outcomes in children and therefore caries management should be considered an approach impacting overall health and quality of life.